Protoptilinae (Trichoptera: Glossosomatidae) from Roraima state, northern Brazil: A new species of Itauara Müller 1888 and new distributional records for species of Protoptila Banks 1904 - Neto, Jaime De Liege Gama; Passos, Mahedy Araujo Bastos (Zootaxa, 2023)
A new species of caddisfly, Itauara marcellina sp. nov., is described and illustrated from Roraima state in northern Brazil. This new species is characterized by features of the male genitalia. The dorsolateral processes of tergum X, in dorsal view, are horn-like and the phallicata has a medial pair of membranous, rounded, lateral flanges projecting posteroventrad. Protoptila ctenacantha Flint 1974 is recorded for the first time from Brazil. Protoptila condylifera Flint 1971, Protoptila flexispina Flint 1971, Protoptila simplex Flint 1971, and Protoptila trispicata Flint 1971 are recorded for the first time from Roraima state, Brazil.